Comparison of Corruption Criminal Law in Indonesia and China: Analysis of Sanctions and Implementation - Sumunar, Sumertak; Sunaryo, Sidik; Haris (Faculty of Law, Universitas Pekalongan, 2024)
Corruption is a serious problem that affects stability and development in many countries, including Indonesia and China. These two countries have different approaches in terms of regulating sanctions and implementing punishments against corrupt actors. This study aims to conduct a comparative analysis of how the criminal law of corruption is regulated and implemented in Indonesia and China. Departing from the above problems, the author takes three formulations, the first problem is how the regulation of the threat of death penalty in corruption crimes in Indonesia and China differs? Second, how is the regulation of the threat of death penalty in corruption crimes in Indonesia and China similar? And third, how does the regulation of the threat of death penalty in corruption crimes in Indonesia compare with China? In this study, the author uses a normative research method, which is often referred to as doctrinal legal research or literature research. The results of this study are that overall, China tends to have heavier and stricter criminal sanctions in dealing with corruption compared to Indonesia, with the use of the death penalty being an option in extreme cases. On the other hand, Indonesia has shown a focus on restoring state losses and additional law enforcement to increase effectiveness and accountability in the eradication of corruption. Although China's approach to corruption punishment is very firm, not all elements can be adapted to improve the system in Indonesia Keywords:Corruption Criminal Law; China; Indonesia